PENGEMBANGAN LKM (LEMBAR KERJA MAHASISWA) MATERI BIOTEKNOLOGI PANGAN MELALUI EKSPERIMEN KUALITAS SUSU TEMPE BUBUK DENGAN LAMA FERMENTASI - Apriyani '; Imam Mahadi; Darmawati ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The aims of this research todetermine the quality of tempeh milkpowder by time fermentation and designing Student Worksheet relevant to a materialFood Biotechnology Food Fermentation sub material. This study consisted of twophases. The first phase, were the making of tempeh milk powder using the experimentalmethod with completely randomized design (CRD), which consists of 5 treatments and 3replications. Parameters measured were moisture content, protein content, fat content,pH and organoleptic test. The results obtained were analyzed by ANOVA and a furthertest DMRT at 5% level. The second phase were the development of Student Worksheetfrom the results of the first phase. This research used ADDIE development model(Analysis, Design, Development, Implementation and Evaluation) are simplified intophases Analysis, Design and Development. Data of Student Worksheet developmentobtained from the validation sheet which validated by 3 validators with 5 validitycriterias were analyzed descriptively. Results showed that the time of fermentationinfluence on moisture content, protein content, fat content, pH and organoleptic test.Fermentation time 12 hours is a long time to produce the best fermented tempeh milkpowder quality. Which results in moisture content of 0.78%, 2.61% protein content, fatcontent 2.00% and 5.01 pH levels. As for organoleptic texture, color, aroma and flavorcontained in the fermentation 36 hours. Results of the study can be used as StudentWorksheet in the sub materials Food Fermentation on the material Food Biotechnologywith a mean value of 3.32 validity valid category.Keywords : Student Worksheet, Food Biotechnology, Tempeh Milk Powder, TimeFermentation.